Evaluating the effect of prenatal interventions on maternal-foetal attachment: A systematic review and meta‐analysis - Elieh Abasi; Afsaneh Keramat; Narjes Sadat Borghei; Shahrbanoo Goli; Maryam Farjamfar (Wiley, 2021)
Abstract Aim This study aimed to evaluate the effect of prenatal interventions on maternal foetal attachment. Design Systematic review and meta‐analysis. Methods In this study, a comprehensive review was performed to find articles published from January 2000 ‐ December 2019 in the form of randomized and non‐randomized clinical trials. To this end, online databases including PubMed, Scopus, Google Scholar, ScienceDirect, Proquest, Ovid, CINAHL and JAMA were searched. Duplicate articles were also excluded using Endnote X7 Reference. The results were then analysed via RevMan 5.3 software. Results The results showed that foetal movement counting did not seem to be effective in increasing MFA by itself. But, this intervention alongside other attachment behaviours such as touching the belly and talking to foetus could enhance MFA. Therefore, the best interventions to improve MFA might be combined ones implemented in the form of counselling and training sessions.